GROWTH PERFORMANCE AND HEMATOGICAL RESPONSES OF LABEO ROHITA FINGERLINGS TO DIETARY CITRULLUS LANATUS SEED MEAL AS SUBSTITUTE OF SOYBEAN MEAL - SHRIVASTAV, NUPUR; PRAKASH, SUCHETA; ROY, DAYALANAND (Journal of the Inland Fisheries Society of India, 2024)
A 50 day feeding trial was conducted to determine the effects of replacing Soybean meal (SBM) protein with watermelon seed meal (WSM) on growth, feed utilization of Labeo rohita. Four isonitrogenous (30%) diets were applied in four treatment groups designed as WSM0, WSM15, WSM30 and WSM45, Where 0%, 15%, 30% and 45% of SBM protein were substituted by WSM respectively. Significantly higher mean final weight (g), weight gain (%) and specific growth rate was recorded in all treatments. Consequently, significantly lower feed conversion ratio (FCR) was found in all treatments. Moreover, protein content and lipid content of fish muscle tissues were significantly in higher in all treatments. Hemoglobin, Red blood cells and White blood cells were significantly higher in all treatments. Therefore, the results suggest that WSM could replace up to 45% replacement of SBM protein in diets of Labeo rohita without comprising growth performance.